2018
DOI: 10.3390/ijms19092681
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt3a/FOXM1/β-Catenin Axis and Activation of GSK3β and Caspases are Critically Involved in Apoptotic Effect of Moracin D in Breast Cancers

Abstract: Although Moracin D derived from Morus alba was known to have anti-inflammatory and antioxidant activities, the underlying antitumor mechanism of Moracin D has not been unveiled thus far. Thus, in the recent study, the apoptotic mechanism of Moracin D was elucidated in breast cancer cells. Herein, Moracin D exerted significant cytotoxicity in MDA-MB-231 and MCF-7 cells. Furthermore, Moracin D increased sub G1 population; cleaved poly (Adenosine diphosphate (ADP-ribose)) polymerase (PARP); activated cysteine asp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…FOXM1 deubiquitinated by USP21 modulates cell cycle and paclitaxel sensitivity of basal-like breast cancer cells [ 38 ]. Repression of Wnt3a/FOXM1/β-Catenin pathway is widely involved in the apoptotic impact of moracin D in breast cancer [ 39 ]. Consistent with the report of Zhu et al [ 18 ], we verified that FOXM1 was expressed at high levels in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 deubiquitinated by USP21 modulates cell cycle and paclitaxel sensitivity of basal-like breast cancer cells [ 38 ]. Repression of Wnt3a/FOXM1/β-Catenin pathway is widely involved in the apoptotic impact of moracin D in breast cancer [ 39 ]. Consistent with the report of Zhu et al [ 18 ], we verified that FOXM1 was expressed at high levels in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of circRNAs in ceRNA network is universally known to be related to the posttranscriptional regulation of target mRNAs [34][35][36]. The ceRNA mechanism refers to that circRNA can act as a ceRNA to sponge miRNA, so as to regulate mRNA expression [24].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, Moracin D decreased phosphorylation of NF-κB, ERK, and AKT but not p38 and JNK, in DU145 cells (Figure 4c,d). (Hwang et al, 2018), antitumor mechanisms of Moracin D still remain unclear so far. Thus, in the current study, the underlying apoptotic mechanism of Moracin D was explored in prostate cancer cells.…”
Section: Moracin D-activated Ppar-γ/pkc-δ and Reduced The Expression ...mentioning
confidence: 99%
“…Curcumin (Sha et al, 2016), rhizochalinin (Dyshlovoy et al, 2016), apigenin (Erdogan et al, 2016), and icaritin (Hu et al, 2016) showed antitumor effects in prostate cancers. In the same line, though Moracin D, a novel 2-arylbenzofuran flavonoid isolated from the Morus alba, is reported to have hypoglycemic (Basnet, Kadota, Terashima, Shimizu, & Namba, 1993), antiadipogenic (Hu et al, 2016), and antitumor effect only in breast cancer (Hwang et al, 2018), biological studies with Moracin D are still in the beginning so far. Thus, in the current study, the antitumor mechanism of Moracin D was explored in prostate cancer cells in association with PPAR-γ-/PKC-δ-related signaling.…”
mentioning
confidence: 99%